2005
DOI: 10.1074/jbc.m410924200
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Multiple Heparin Binding Growth Factors with Neuropilin-1 and Potentiation of the Activity of Fibroblast Growth Factor-2

Abstract: The hypothesis that neuropilin-1 (Npn-1) may interact with heparin-binding proteins other than vascular endothelial growth factor has been tested using an optical biosensor-based binding assay. The results show that fibroblast growth factor ( ). These results suggest that Npn-1 possesses a "heparin" mimetic site that is able to interact at least in part through ionic bonding with the heparin binding site on many of the proteins studied. Npn-1 was also found to potentiate the growth stimulatory activity of FGF-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
149
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 151 publications
(155 citation statements)
references
References 56 publications
5
149
1
Order By: Relevance
“…A plausible mechanism of NRP1 stimulation of tumor progression in our study and the pancreatic cancer model is that NRP1 enhances endogenous signaling modulating tumor cell function independent of VEGF. Our results of NRP1 potentiation of the HGF/SF/c-Met signaling pathway in glioma cells agree with another recent study showing that that NRP1 not only interacts directly with multiple heparin-binding growth factors, such as FGF-2, FGF-4 and HGF/SF, but also potentiates stimulation of FGF-2 on endothelial cells (West et al, 2005). In addition, the increased sensitivity to HGF/SF/c-Met signaling by endogenously expressed NRP1 in glioma cells is analogous to the increase in sensitivity to FGF-2 caused by the addition of a soluble NRP1 dimer to endothelial cells in the aforementioned study.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…A plausible mechanism of NRP1 stimulation of tumor progression in our study and the pancreatic cancer model is that NRP1 enhances endogenous signaling modulating tumor cell function independent of VEGF. Our results of NRP1 potentiation of the HGF/SF/c-Met signaling pathway in glioma cells agree with another recent study showing that that NRP1 not only interacts directly with multiple heparin-binding growth factors, such as FGF-2, FGF-4 and HGF/SF, but also potentiates stimulation of FGF-2 on endothelial cells (West et al, 2005). In addition, the increased sensitivity to HGF/SF/c-Met signaling by endogenously expressed NRP1 in glioma cells is analogous to the increase in sensitivity to FGF-2 caused by the addition of a soluble NRP1 dimer to endothelial cells in the aforementioned study.…”
Section: Discussionsupporting
confidence: 82%
“…A recent study demonstrated NRP1 also interacts with several heparin-binding growth factors, such as FGF-2, FGF-4 and HGF/SF, and potentiates the growth stimulatory activity of FGF-2 on endothelial cells (West et al, 2005). As HGF/SF and FGF-2 were shown to stimulate cell growth through receptor-mediated autocrine signaling in glioma cells (Abounader and Laterra, 2005), we performed enzyme-linked immunosorbent assay (ELISA) and determined whether the autocrine signaling activities of these growth factors were involved in the NRP1-stimulated U87MG cell survival and growth.…”
Section: Nrp1 Promotes U87mg Cell Growth Through Enhancing Autocrine mentioning
confidence: 99%
See 1 more Smart Citation
“…FGF signaling plays an important role in branching morphogenesis (Affolter et al, 2009), including morphogenesis of the mammary gland (Lu et al, 2006). Interestingly, however, FGF-induced branching of mammary epithelial cells does not appear to involve NRP2, although there is evidence that the NRPs can interact with and modulate the function of specific heparin-binding factor receptors, including FGF receptors (West et al, 2005).…”
Section: Research Articlementioning
confidence: 99%
“…In contrast, overexpression of NRP-1 leads to over-stimulation of blood vessel formation (Kitsukawa et al, 1995). Studies have shown that NRP-1interacts with a subset of heparin binding proteins like FGF-1, FGF-2, FGF-4, FGF-7, FGF receptor-1, and HGF/SF (West et al, 2005). Investigation of the role of NRP-1 in human glioma progression, Hu et al (Hu et al, 2007) have shown that NRP-1 expression correlates with tumor progression in clinical setting, and that NRP-1 expression promotes tumor growth and survival through an autocrine HGF/SF/c-met signaling pathway.…”
Section: On the Role Of Cell Surface Chondroitin Sulfates And Their Cmentioning
confidence: 99%